Improving thermal and mechanical properties of biomass-based polymers using structurally ordered polyesters from ricinoleic acid and 4-hydroxycinnamic acids. Issue 60 (12th October 2020) - Yamamoto, Atsushi; Nemoto, Koji; Yoshida, Masaru; Tominaga, Yuichi; Imai, Yusuke; Ata, Seisuke; Takenaka, Yasumasa; Abe, Hideki; Sato, Kazuhiko
Abstract : The synthesis of structurally ordered polyesters derived from ricinoleic acid and 4-hydroxycinnamic acids improves the thermal and mechanical properties. Abstract : Biomass-based copolymers with alternating ricinoleic acid and 4-hydroxycinnamic acid derivatives ( p -coumaric acid, ferulic acid, and sinapinic acid) exhibit a repeating structure based on soft and hard segments, derived from ricinoleic and 4-hydroxycinnamic acids, respectively. To achieve this alternating sequence, copolymers were synthesised by the self-condensation of hetero-dimeric monomers derived by the pre-coupling of methyl ricinolate and 4-hydroxycinnamic acid. The glass transition temperature ( T g ) was observed to increase as the number of methoxy groups on the main chain increased; the T g values of poly(coumaric acid- alt -ricinoleic acid), poly(ferulic acid- alt -ricinoleic acid), and poly(sinapinic acid- alt -ricinoleic acid) are −15 °C, −4 °C, and 24 °C respectively, 58 °C, 69 °C, and 97 °C higher than that of poly(ricinoleic acid). The polymers were processed into highly flexible, visually transparent films. Among them, poly(sinapinic acid- alt -ricinoleic acid) bearing two methoxy groups on each cinnamoyl unit, is mechanically the strongest polymer, with an elastic modulus of 126.5 MPa and a tensile strength at break of 15.47 MPa.